From Extraction to Inclusion: How Indonesia’s Bauxite Downstreaming Shapes Decent Work and Economic Growth - Fiya Ainur Rohmatika; Arie Kusuma Paksi (Jurnal Mamangan, 2023)
Indonesia is one of the world's largest bauxite producers, which since 2023 has implemented a policy prohibiting the export of raw ore as part of its national mineral downstreaming strategy. This policy aims to increase domestic added value, strengthen economic sovereignty, and support the achievement of Sustainable Development Goal (SDG) 8 on decent work and inclusive economic growth. This study aims to analyze the implementation of Indonesia's bauxite downstreaming policy from the perspective of international political economy and sustainable development diplomacy, highlighting economic, social, and institutional dimensions. The method used is a qualitative approach through policy analysis, secondary data from BPS, ESDM, and international scientific publications. The results show that the national alumina refining capacity increased from 1.4 million tons in 2021 to ±5.3 million tons in 2024, accompanied by an expansion of foreign investment, mainly from China. However, this increase in capacity has not been fully accompanied by an improvement in job quality, as 61% of workers in this sector are still on contract with limited skills upgrading. In addition, institutional inequality and the dominance of foreign investors indicate the continued weakness of national control in the global alumina value chain. In conclusion, the downstreaming of Indonesian bauxite has contributed to economic growth and sustainable industrial diplomacy, but its success depends on institutional reform, strengthening national technology, and integrating social aspects so that the transition from extraction to inclusive industrialization can truly be realized in a fair and sustainable manner.